Adsorption and photocatalytic degradation of tetracycline and byproduct sweeping on rotating TiO2-coated aluminum drum - Bautista, Ramer P. (College of Engineering, University of the Philippines Diliman, 2016)
The presence, abundance and persistence of antibiotics in ground and surface waters pose health risks by developing resistance genes m mlcroorgamsms. When antimicrobial resistance (AMR) is developed, these microorganisms cannot be treated by the existing drugs. One of the most commonly found antibiotics in the wastewater is tetracycline (TC). Studies on advance oxidation processes are being conducted to remove TC from wastewater. This study investigates the adsorption and surface reaction of TC with immobilized titanium dioxide (TiO2) on aluminum drum surface. Photocatalytic activity was explored using UV irradiation. The experiments were perfonned by immersing a portion of rotating smooth-surfaced (SSD) and corrugated (CAD) aluminum drums in a trough of TC solution. Bare and TiOz-coated CADs were used to expose adhering TC solution to VV lamps above the reactor to evaluate the photon effects. The TC and its degradation byproducts were detected and measured by spectrophotometry, liquid chromatography tandem with mass spectrometry (LCMS) using dual ion source (DUlS), and antimicrobial assay using disc diffusion method against Pseudomonas aeruginosa as test organism. Results show that TC adsorption on drum surface follows Langmuir isotherm, which implies monolayer adsorption. Using bare aluminum drums, the TC removal in the first 20 min is characterized by rapid adsorption. The succeeding removal is slow due to saturation and slow surface reaction with Al3+, serving as the Lewis acid site for TC transfonnation The UV-assisted aluminum adsorption (no TiO2) was found to be more effective than adsorption alone. The UV might have provided energy to excite and eventually break the bond between the aluminum site and TC degradation byproducts resulting in faster desorption and faster availability of aluminum sites for further adsorption and TC transformation. The degradation byproducts based on the LCMS analysis are similar, which propose the same mechanism with only difference in reaction rates. In the presence of TiO2, the adsorption rate was faster and more effective because of additional sites for adsorption and surface reaction. However, in the presence of TiO2 and UV, the TC removal has faster reaction rate and more effective degradation. The LCMS analysis proved that there were more degradation species but the major byproducts remaining in the solution are similar with the other treatment schemes. The two major TC byproducts in the treatment were m/z 234.95 and m/z 195.00. The "sweeping" mechanism of photocatalysis was effective to desorb the byproducts bonded to the aluminum and TiO2. After desorption, the sites become available again for more adsorption and photocatalytic degradation. The relationship between operational parameters and the reactor treatment performance was investigated. A 2^5 full factorial design of experiment was conducted to understand the main and interaction effects of initial TC concentration, drum rotation speed, UV irradiance, TiO2 immobilization and drum corrugation. The factorial regression model proposes that the initial TC concentration, TiO2 immobilization, drum corrugation and irradiation level have positive main effects to the TC removal efficiency. The drum corrugation, on the other hand, has positive interaction effect with initi al TC concentration and negative interaction effect with TiO2 immobilization. This shows that these factors have significant interaction effects. At higher initial TC concentration, the rate of TC adsorption on the aluminum sites is faster. These relation ships were optimized to attain the maximum treatment efficiency of the reactor. The optimized condition was achieved with 40-ppm initial TC concentration, 17.66-rpm drum speed, one 40-W UV lamp for irradiation, and TiO2-coated CAD. This condition was expected to remove 94.47% of initial TC after 120 min of operation. The validation was conducted and the initial result was 94.21 % TC removal after 60 min. The operation was performed for 45 times to observe its reusability. After 45 batches using the same reactor, the average TC removal was 85.14% with 5.78% standard deviation. The results suggest that the adsorption and the sweeping mechanism are effective for long-term use of the reactor. The optimized condition was also validated using antimicrobial assay against Pseudomonas aeruginosa. The potency of the solution quickly dropped after 10 min and eventually lost after 20 min. This confirms the TC degradation and this also implies that the byproducts are not potent against the bacteria. The study concludes that high TC removal efficiency can be achieved by rapid adsorption on aluminum and TiO2 and effective photocatalytic degradation of TC and sweeping of the by products.